O uso do omnichannel em pequenas e médias empresas: um estudo sobre a sua aplicação no varejo - Oliveira, Henrique Diez Marques de (2022)
The goal of this study is to investigate the possibility of using omnichannel in small and medium-sized retail companies, as well the benefits and challenges involved in the application. For that, a survey with semi-structured interviews was conducted with three specialists in retail and omnichannel in Brazil. Among the main results, it is highlighted that omnichannel is an important and applicable strategy for large companies and small and medium-sized companies in the retail sector. In addition, it was found that the application of omnichannel brings benefits such as a reduction of the logistical costs and an increase of the company's profit, making the organization able to carry out more assertive campaigns to its customers and provide a unique experience journey to the consumer. About the challenges, small and medium-sized companies may face the high costs involved for implementation, as well as a limiting culture of their employees, who need to be able to make this change for their application. The main contribution of this study is to understand the use of omnichannel as a competitive advantage for companies, even if they are small or medium-sized.